We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**+10 **

$$\\-48+9(x^4-x)=6(12-x)+9x^4\\

-48+9x^4-9x=72-6x+9x^4\\

-48-9x=72-6x\\

$add 6x to both sides$\\

-48-3x=72\\

$add 48 to both sides$\\

-3x=120\\

x=-40$$

Melody Dec 23, 2014

#4**+5 **

**-48+9(x4−4x)=6(12−x)+9x4-48+9x4−36x=72−6x+9x4-48+9x4=72+30x+9x4-120+9x4=30x+9x4-120=30x-4=x**

shaniab29544 Dec 23, 2014

#5**+5 **

I cannot make sense of what you have done Shaniab.

Remember - one equal sign per line - NEVER MORE

Melody Dec 23, 2014